Path Planning of Mobile Robot Using Fuzzy- Potential Field Method - Ahmed, Alaa A.; Abdalla, Turki Y.; Member), Ali A. Abed (IEEE (Iraqi Journal for Electrical and Electronic Engineering, 2015)
This paper deals with the navigation of a mobile robot in unknown environment using artificial potential field method. The aim of this paper is to develop a complete method that allows the mobile robot to reach its goal while avoiding unknown obstacles on its path. An approach proposed is introduced in this paper based on combing the artificial potential field method with fuzzy logic controller to solve drawbacks of artificial potential field method such as local minima problems, make an effective motion planner and improve the quality of the trajectory of mobile robot.